Oxidation of 3, 5-di-C-(per-O-acetylglucopyranosyl)phloroacetophenone in the synthesis of hydroxysafflor yellow A. (7th August 2017) - Suzuki, Toshiyuki; Ishida, Mitsuo; Kumazawa, Toshihiro; Sato, Shingo
Abstract: In the synthesis of the main yellow pigment hydroxysafflor yellow A (HSYA), that is present in safflower petals, the key compound 4-( S )-2-acetyl-4, 6-di- C -(per- O -acetyl-β-D-glucosyl)-3, 4-dihydroxy-5-methoxycyclohexa-2, 5-dienone (11b ) was diastereoselectively synthesized in an overall yield of 18% from di- C -β-D-glucosylphloroacetophenone per- O -acetate (8 ). Graphical abstract: Highlights: The structure of the main yellow component in safflower petals has been discussed. The compound di- C -glycoside HSYA undergoes an intramolecular condensation. A key compound in the synthesis of HSYA is a 4-( S )-di- C -glucosylquinol. 4-( S )-di- C -glucosylquinol was synthesized via diastereoselective oxidation. Configuration of the new stereocenter was determined by circular dichroism.